2016
DOI: 10.1017/jrc.2016.1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Validation of the Taiwanese Version of theJob Satisfaction of Persons with Disabilities Scalein a Sample of Individuals with Poliomyelitis

Abstract: Objective: To evaluate the measurement structure of the Taiwanese Version of theJob Satisfaction of Persons with Disabilities Scale(JSPDS).Design: A quantitative descriptive research design using exploratory factor analysis (EFA).Participants: One hundred and thirty-two gainfully employed individuals from Taiwan with poliomyelitis participated in this study.Results: EFA result indicated a three-factor structure accounting for 54.1 per cent of the total variance. The internal consistency reliability coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The total score was averaged with higher scores indicating a higher level of job satisfaction. Smedema et al (2016) validated this scale for use with people with disabilities and reported a three-factor structure: (a) integrated work environment, (b) job quality, and (c) alienation with Cronbach's alpha internal consistency reliability coefficients for the integrated work environment, job quality, and alienation to be .91, .77, and .59, respectively. The 14-item scale was adapted and validated by a group of researchers and peer support specialists in an attempt to enhance the usefulness and appropriateness of the scale for peer support specialists, which also reported a Cronbach's alpha of .83 for the total scale (Brooks et al, 2021).…”
Section: Occupational Healthmentioning
confidence: 99%
“…The total score was averaged with higher scores indicating a higher level of job satisfaction. Smedema et al (2016) validated this scale for use with people with disabilities and reported a three-factor structure: (a) integrated work environment, (b) job quality, and (c) alienation with Cronbach's alpha internal consistency reliability coefficients for the integrated work environment, job quality, and alienation to be .91, .77, and .59, respectively. The 14-item scale was adapted and validated by a group of researchers and peer support specialists in an attempt to enhance the usefulness and appropriateness of the scale for peer support specialists, which also reported a Cronbach's alpha of .83 for the total scale (Brooks et al, 2021).…”
Section: Occupational Healthmentioning
confidence: 99%
“…Gainful employment is defined as a job position for which employees receive steady work and payment from their employers. The financial, psychological, social, and health rewards of gainful employment are well documented (Fryers, 2006;Helliwell et al, 2020;Smedema et al, 2016). More specifically, individuals, including veterans, who are gainfully employed enjoy higher levels of physical health, mental health, and life satisfaction than unemployed ones (Helliwell et al, 2020;Kamerāde et al, 2019;Umucu, Reyes, Nay, et al, 2021).…”
mentioning
confidence: 99%